Upaya Meningkatkan Pemahaman Dhamir Menggunakan Metode Qowaid wa Tarjamah SMP Qur’an Darul Fattah Bandar Lampung - Muhammad Irham (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
This research is based on the weakness of students in understanding Arabic materials, including translating Arabic texts and understanding Arabic rules. Therefore, the researcher made an alternative solution by applying the Qowaid wa Tarjamah method, which is a method that emphasizes grammatical analysis and translating Arabic texts. he formulation of the problem in this study is whether using the Qowaid wa Tarjamah method can improve understanding of Arabic and how to improve Arabic understanding of pronouns (dhamir) using the Qowaid wa Tarjamah method. The aim is to improve students' understanding of learning Arabic and apply the Qowaid wa Tarjamah method in the learning process. This type of research uses classroom action research (PTK). This research was conducted in class VII Hafshah SMP Qur'an Darul Fattah Bandar Lampung in the 2019/2020 school year. With 25 female students. This research was conducted in 2 cycles with 4 meetings in each cycle. In this study, it was obtained that the average student learning outcomes in the pre-cycle was 56.84, cycle 1 was 74.64 and cycle 2 was 85.16. Based on these results it can be concluded that using the Qowaid wa tarjamah method can improve students' understanding of Arabic about the material of dhamir muttashil class VII students of Hafshah Qur'an Darul Fattah Junior High School in Bandar Lampung. What researchers do in using this method is to convey the concept of dhamir, provide examples, memorize definitions and translate Arabic texts. Keywords: PTK, Dhamir, Qowaid wa Tarjamah, Understanding.